Anticorruption efforts and corporate fraud - Na Zou (ZBW - Leibniz Information Centre for Economics, 2020)
This study examines whether and how anticorruption efforts may mitigate the risk of corporate fraud. Based on a sample of Chinese publicly listed firms over the period of 2008 to 2017, we find that anticorruption efforts reduce the likelihood of fraud commission and increase the likelihood of detection given fraud. These effects are driven by state-owned enterprises and politically connected firms through politician board members. We also find that firms located in regions with well-developed market and legal institutions are less likely to commit fraud in the post anticorruption period. Firms increasing internal monitoring by appointing local independent directors with accounting background help to explain the reduction of fraud in these regions. This study contributes to the literature on corporate wrongdoing and the design of strategies to mitigate the risk of corporate fraud in an emerging economy context.
Keywords: G30; G34; K22; 330; Corporate fraud; Anticorruption; Corporate governance; Firm heterogeneity; Internal monitoring